Heart Rate Recovery After Exercise Is Associated With Arrhythmic Events in Patients With Catecholaminergic Polymorphic Ventricular Tachycardia. (March 2020) - Lieve, Krystien V.V.; Dusi, Veronica; van der Werf, Christian; Bos, J. Martijn; Lane, Conor M.; Stokke, Mathis Korseberg; Roston, Thomas M.; Djupsjöbacka, Aurora; Wada, Yuko; Denjoy, Isabelle; Bundgaard, Henning; Noguer, Ferran Roses I.; et al.
Abstract : Background: Risk stratification in catecholaminergic polymorphic ventricular tachycardia remains ill defined. Heart rate recovery (HRR) immediately after exercise is regulated by autonomic reflexes, particularly vagal tone, and may be associated with symptoms and ventricular arrhythmias in patients with catecholaminergic polymorphic ventricular tachycardia. Our objective was to evaluate whether HRR after maximal exercise on the exercise stress test (EST) is associated with symptoms and ventricular arrhythmias. Methods: In this retrospective observational study, we included patients ⩽65 years of age with an EST without antiarrhythmic drugs who attained at least 80% of their age- and sex-predicted maximal HR. HRR in the recovery phase was calculated as the difference in heart rate (HR) at maximal exercise and at 1 minute in the recovery phase (ΔHRR1′). Results: We included 187 patients (median age, 36 years; 68 [36%] symptomatic before diagnosis). Pre-EST HR and maximal HR were equal among symptomatic and asymptomatic patients. Patients who were symptomatic before diagnosis had a greater ΔHRR1′ after maximal exercise (43 [interquartile range, 25–58] versus 25 [interquartile range, 19–34] beats/min; P <0.001). Corrected for age, sex, and relatedness, patients in the upper tertile for ΔHRR1′ had an odds ratio of 3.4 (95% CI, 1.6–7.4) of being symptomatic before diagnosis ( P <0.001). In addition, ΔHRR1′ was higher in patients with complex ventricular arrhythmias at EST off antiarrhythmic drugs (33 [interquartile range, 22–48] versus 27 [interquartile range, 20–36] beats/min; P =0.01). After diagnosis, patients with a ΔHRR1′ in the upper tertile of its distribution had significantly more arrhythmic events as compared with patients in the other tertiles ( P =0.045). Conclusions: Catecholaminergic polymorphic ventricular tachycardia patients with a larger HRR following exercise are more likely to be symptomatic and have complex ventricular arrhythmias during the first EST off antiarrhythmic drug. Abstract : Supplemental Digital Content is available in the text.